FORMATION OF AN INTEGRATED MANAGEMENT SYSTEM IN THE CONTEXT OF INNOVATIVE MANAGEMENT DEVELOPMENT - D. G. Rodionov; S. M. Daniali; T. V. Mokeeva (Вестник университета)
The issue of integrated management system formation in the context of innovative management development has been considered. The concept of an integrated management system has been clarified and an integrated management system version, which is based on the integration of existing management standards and integrates their policies and strategies into a common basic management principle, has been proposed. A conceptual multiply connected model of an integrated management system and a model with managerial innovations as part of an integrated management system have been developed. The factors influencing the motivation for creating and improving an integrated management system have been presented. The problems of searching for integrative areas of interaction between management standards have been considered and a matrix of interaction between management standards has been proposed.